Recyclable CFRPs with extremely high Tg: hydrothermal recyclability in pure water and upcycling of the recyclates for new composite preparation. Issue 29 (12th July 2022) - Hao, Cheng; Liu, Tuan; Liu, Wangcheng; Fei, Ming-en; Shao, Lin; Kuang, Wenbin; Simmons, Kevin L.; Zhang, Jinwen
Abstract : In this work, a recyclable epoxy system with superior mechanical performance and high T g (>200 °C) is developed for CFRPs, and a simple and feasible approach for highly efficient closed-loop recycling of CFRPs is demonstrated. Abstract : In recent years researchers have introduced different malleable and/or degradable thermosetting polymers to address the recyclability of traditional thermoset materials. Nonetheless, the mechanical properties and glass transition temperature ( T g ) of these polymers are often compromised to achieve the desired depolymerization rate. In this work, a hydrothermally recyclable epoxy/anhydride thermosetting system with superior mechanical performance and high T g (>200 °C) was developed for carbon fiber reinforced plastic (CFRP) applications, using triethanolamine as the co-curing agent and tetraglycidyl methylenedianiline (TGDDM) as the epoxy matrix. The hydrothermal recycling of such cured systems is achieved at relatively low temperature (200 °C) without the addition of a catalyst. This mild recycling process decomposes the recyclable polymer matrix into an oligomer and imparts little damage to the valuable carbon fiber. The recycled carbon fiber and the decomposed polymer resin are reused to prepare a new CFRP. Therefore, this study has introduced a simple and practical approach for the preparation of recyclable CFRPs with high T g and a pathway for highly efficient closed-loop recycling, which sets up a framework for the future design of sustainable polymer composites.